2020
DOI: 10.1111/evo.13932
|View full text |Cite
|
Sign up to set email alerts
|

Environmental stress maintains trioecy in nematode worms

Abstract: Sex is determined by chromosomes in mammals but it can be influenced by the environment in many worms, crustaceans, and vertebrates. Despite this, there is little understanding of the relationship between ecology and the evolution of sexual systems. The nematode Auanema freiburgensis has a unique sex determination system in which individuals carrying one X chromosome develop into males while XX individuals develop into females in stress‐free environments and self‐fertile hermaphrodites in stressful environment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In laboratory cultures, XO males are in lower proportions (typically 5–15%) than XX non-males (females and hermaphrodites) ( Félix, 2004 ; Chaudhuri et al, 2011a , 2015; Shakes et al, 2011 ; Robles et al, 2021 ). The dynamics of this unusual mating system is poorly understood ( Anderson et al, 2020 ; Rupp, 2020 ). In the species described so far, Auanema rhodensis (aka Rhabditis sp.…”
mentioning
confidence: 99%
“…In laboratory cultures, XO males are in lower proportions (typically 5–15%) than XX non-males (females and hermaphrodites) ( Félix, 2004 ; Chaudhuri et al, 2011a , 2015; Shakes et al, 2011 ; Robles et al, 2021 ). The dynamics of this unusual mating system is poorly understood ( Anderson et al, 2020 ; Rupp, 2020 ). In the species described so far, Auanema rhodensis (aka Rhabditis sp.…”
mentioning
confidence: 99%
“…Contrary to work that has suggested trioecy (males, females, and hermaphroditic individuals) is a transitory state (Lande & Schemske, 1985), Anderson et al. (2020) has shown that trioecy can be stable and reap the benefits of outcrossing and reproductive assurance. Yet, understanding reproductive system variation necessitates integrative ecological and genetic approaches to disentangle the forces that drive transitions in sexual system (see Table 1) and how that influences the reproductive system.…”
Section: Reproductive Diversitymentioning
confidence: 86%
“…In disturbed habitats, such as those where frequent extinction and colonization events occur, monoecious individuals will have a selective advantage, as only one individual is necessary to (re-)establish the population (Baker, 1955). Contrary to work that has suggested trioecy (males, females, and hermaphroditic individuals) is a transitory state , Anderson et al (2020) has shown that trioecy can be stable and reap the benefits of outcrossing and reproductive assurance. Yet, understanding reproductive system variation necessitates integrative ecological and genetic approaches to disentangle the forces that drive transitions in sexual system (see Table 1) and how that influences the reproductive system.…”
Section: Intergametophytic Crossingmentioning
confidence: 88%
“…The trioecic condition has been recorded so far only in some animals, such as a few nematode species and a hydra 9 , 10 , 14 , 46 48 . In marine invertebrates, it has been reported in one anemone under laboratory conditions and in one bivalve mollusk 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%